High-pressure synthesis of seven lanthanum hydrides with a significant variability of hydrogen content - Dominique Laniel; Florian Trybel; Bjoern Winkler; Florian Knoop; Timofey Fedotenko; Saiana Khandarkhaeva; Alena Aslandukova; Thomas Meier; Stella Chariton; Konstantin Glazyrin; Victor Milman; Vitali Prakapenka; et al. (Nature Communications, 2022)
The lanthanum-hydrogen system has attracted attention following the observation of superconductivity in LaH10 at near-ambient temperatures and high pressures. Here authors describe the high-pressure syntheses of seven La-H phases; they report crystal structures and remarkable regularities in rare-earth element hydrides.